PERANCANGAN FORMULASI DAN IMPLEMENTASI STRATEGI BISNIS PADA UMKM DAPURATU DI SUBANG - Sopiawadi, Mutqi; Baruni, Maulidya Bilqies; Herliana, Fatihah; Putri, Dahlia Novita; Puspa, Welga (MAJU : Indonesian Journal of Community Empowerment, 2025)
This study aims to design the formulation and implementation of business strategies in DapuRatu MSMEs located in Subang, with a focus on developing sustainable and competitive culinary businesses. In facing increasingly competitive market challenges, DapuRatu needs the right strategy to improve product quality, service, and competitiveness. This study uses a SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis approach to identify internal and external factors that affect business performance and formulate appropriate strategies to optimize business potential. The results of the study indicate that DapuRatu's strengths lie in its strategic location, affordable prices, and good service quality. However, the company also faces challenges such as the number of competitors and lack of product innovation. By taking advantage of existing opportunities, such as increasing the tourism sector in Subang, DapuRatu can develop new, innovative menus and increase market reach through online platforms. In addition, effective marketing strategies and good financial management are needed to ensure sustainable growth.